Assessing the applicability of a smeared crack approach for simulating the behaviour of concrete beams flexurally reinforced with GFRP bars and failing in shear - Barros, Joaquim A. O. (2021)
Numerical simulation of beams failing in shear is still a challenge. With the scope of verifying the applicability of smeared crack approaches to simulate the behavior of reinforced concrete (RC) beams failing in shear, a set of concrete beams reinforced with longitudinal glass fiber reinforced polymer (GFRP) bars, experimentally tested up to their failure, and comprehensibly monitored, are numerically simulated. The simulations are carried out with a multi-directional fixed smeared crack model available in the FEMIX computer program that has several options for modeling the crack shear stress transfer, which is a critical aspect when simulating RC elements failing in shear. The predictive performance of the numerical simulations is assessed in term of load vs deflection, crack pattern at failure, concrete strains in critical shear regions, and moment–curvature relationship. The influence on the predictive performance of the following modeling aspects is also investigated: finite element mesh refinement; simulation of the crack shear stress transfer by using the classical shear retention factor and a crack shear-softening diagram; bond conditions between flexural reinforcement and surrounding concrete. The simulations carried out demonstrate that small dependence of the results on the finite element mesh refinement and adequate crack patterns can be obtained with refinement levels suitable for design purposes and taking into account the actual computer performances, as long as a crack shear-softening diagram is used. However, the predictive performance of the simulations depends significantly on the values adopted for the parameters that define this diagram, as demonstrated by the performed parametric studies.